88.0k views
0 votes
Simplify

(2x– 3) (5x4 – 7x3 + 6x2 – 9)



A. 10x5 – 29x4 + 33x3 - 18x2 18x + 27
B. 10x5 - x4-9x3 – 18x2 -18x - 27
C. 10x5 + 29x4 – 33x3 + 18x2 + 18x - 27
D. 10x5 + x4 + 33x3 + 18x2 + 18x + 27

User Thclpr
by
5.2k points

2 Answers

4 votes

Answer:

=(2x+−3)(5x4+−7x3+6x2+−9)

=(2x)(5x4)+(2x)(−7x3)+(2x)(6x2)+(2x)(−9)+(−3)(5x4)+(−3)(−7x3)+(−3)(6x2)+(−3)(−9)

=10x5−14x4+12x3−18x−15x4+21x3−18x2+27

=10x5−29x4+33x3−18x2−18x+27

Explanation:

User Luca Putzu
by
5.3k points
5 votes

Answer: (A)=10x5−29x4+33x3−18x2−18x+27

Explanation:

How i solved it was by simplifying each answer there was available and (A) was the most compatiable answer!

=(2x+−3)(5x4+−7x3+6x2+−9)

=(2x)(5x4)+(2x)(−7x3)+(2x)(6x2)+(2x)(−9)+(−3)(5x4)+(−3)(−7x3)+(−3)(6x2)+(−3)(−9)

=10x5−14x4+12x3−18x−15x4+21x3−18x2+27

=10x5−29x4+33x3−18x2−18x+27

User James Burton
by
5.4k points